2023
DOI: 10.1681/asn.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnesium Supplementation on Vascular Calcification in CKD: A Randomized Clinical Trial (MAGiCAL-CKD)

Abstract: Significance Statement Magnesium prevents vascular calcification in animals with CKD. In addition, lower serum magnesium is associated with higher risk of cardiovascular events in CKD. In a randomized, double-blinded, placebo-controlled trial, the authors investigated the effects of magnesium supplementation versus placebo on vascular calcification in patients with predialysis CKD. Despite significant increases in plasma magnesium among study participants who received magnesium compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Besides, a randomized clinical trial (RCT) enrolling 125 subjects showed that oral Mg oxide supplement retarded the progression of coronary artery calcification in patients with CKD 46 . However, another RCT revealed that Mg supplementation for 12 months was not effective in slowing the VC progression in CKD 47 . More studies are needed to explore the optimal dose, duration, and timing of Mg supplementation in the prevention or treatment of VC in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a randomized clinical trial (RCT) enrolling 125 subjects showed that oral Mg oxide supplement retarded the progression of coronary artery calcification in patients with CKD 46 . However, another RCT revealed that Mg supplementation for 12 months was not effective in slowing the VC progression in CKD 47 . More studies are needed to explore the optimal dose, duration, and timing of Mg supplementation in the prevention or treatment of VC in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…A minor but substantial improvement in vascular calcification was seen in the magnesium carbonate group in an open-label trial [36]. However, the preliminary results of the Magical trial suggest magnesium had no effect on coronary artery calcification [37]. The relationship between blood magnesium levels, which may be increased by magnesium carbonate [38], and the risk of all-cause and cardiovascular mortality in CKD patients remains under dispute [39].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium has been shown to prevent vascular calcification in animal models and may lower cardiovascular events in patients with CKD. Bressendorf and colleagues used magnesium hydroxide supplementation for 12 months in an RCT (Effects of Magnesium Supplementation on Vascular Calcification in Chronic Kidney Disease [MAGiCAL-CKD]) on 148 patients with CKD to explore its impact on vascular calcification [30]. In this study, magnesium hydroxide supplementation (15 mmol twice daily) did not slow progression of coronary artery calcification score despite a significant increase in serum levels.…”
Section: Hypertension Vascular Calcification and Morementioning
confidence: 99%